Association between the atherogenic index of plasma and abdominal aortic calcification: results from the National Health and Nutrition Examination Survey 2013–2014 - Su, Xiaozhou; Zhao, Chunli; Li, Donghua; Zhang, Xianwei (Frontiers in Endocrinology, 2025)
BackgroundCoronary artery calcification and cardiovascular disease are associated with elevated levels of atherogenic plasma index (AIP). However, the relationship with abdominal aortic calcification (AAC) remains unclear. This study aimed to explore the association between AIP and AAC using the National Health and Nutrition Examination Survey (NHANES) database.MethodsA cross-sectional analysis was conducted on 2,811 individuals aged 40 years or older from the 2013–2014 NHANES dataset. Participants with missing AAC-24 scores, AIP data, or covariate information were excluded. AAC was quantified using the Kauppila score (AAC-24), with a score > 0 indicating the presence of AAC, and severe AAC (SAAC) being defined as an AAC-24 score ≥ 6. Multivariable regression models and restricted cubic spline analyses were employed to assess the associations between AIP and AAC. Sensitivity analysis was used to validate the robustness of the findings.ResultsThe study population had a mean age of 57.7 years, with 48.22% being male. A significant positive association was found between AIP and both the AAC score and the risk of AAC and SAAC, particularly in females. For the overall population, each unit increase in AIP was associated with an overall increase in AAC-24 score of 0.90 (95% CI: 0.22, 1.58; p = 0.009), and for women, the AAC risk and SAAC risk would be 4.01-fold higher (95% CI: 1.65, 9.74; p = 0.002) and 9.37-fold higher (95% CI: 2.37, 37.03; p = 0.001). No significant associations were found in males. Further analysis revealed a significant interaction between AIP and gender regarding both AAC scores and the risk of SAAC.ConclusionsThis study demonstrates a positive relationship between AIP and increased AAC scores, as well as a higher risk of AAC and SAAC in U.S. women. However, these findings require further investigation to confirm the observed gender-specific differences.